2017
DOI: 10.1523/jneurosci.0563-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Self-Grounded Vision: Hand Ownership Modulates Visual Location through Cortical β and γ Oscillations

Abstract: Vision is known to be shaped by context, defined by environmental and bodily signals. In the Taylor illusion, the size of an afterimage projected on one's hand changes according to proprioceptive signals conveying hand position. Here, we assessed whether the Taylor illusion does not just depend on the physical hand position, but also on bodily self-consciousness as quantified through illusory hand ownership. Relying on the somatic rubber hand illusion, we manipulated hand ownership, such that participants embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Together, our results extend the recent studies documenting the impact of the bodily self on low-level vision (Faivre et al, 2017; see Faivre, Salomon & Blanke, 2015 for review), and semantic processing of words (Canzoneri et al, 2016;Noel, Blanke, Serino & Salomon, 2017), by further showing that the . CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Resultssupporting
confidence: 89%
“…Together, our results extend the recent studies documenting the impact of the bodily self on low-level vision (Faivre et al, 2017; see Faivre, Salomon & Blanke, 2015 for review), and semantic processing of words (Canzoneri et al, 2016;Noel, Blanke, Serino & Salomon, 2017), by further showing that the . CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Resultssupporting
confidence: 89%
“…One distinct way that non-H parts of brain affect handwriting is that visual illusions of hand ownership alter connectivity between H and inferior parietal cortex (Faivre et al, 2017…”
Section: Expression Of Personality In Handwritingmentioning
confidence: 99%
“…Hand ownership is also a key factor in the extent to which the visual percept can be changed. Faivre et al (2017) used a combination of positive after images and a version of the RHI called the somatic rubber hand illusion. In this variation of the RHI, an illusion of self-touch is created by having a participant touch a fake hand with their right hand, while at the same time their left hand is being touched in synchrony by the experimenter (Ehrsson, Holmes, & Passingham, 2005).…”
Section: Positive Afterimagesmentioning
confidence: 99%
“…In this variation of the RHI, an illusion of self-touch is created by having a participant touch a fake hand with their right hand, while at the same time their left hand is being touched in synchrony by the experimenter (Ehrsson, Holmes, & Passingham, 2005). In the experiment by Faivre et al (2017) they tested whether drifts in the afterimage of an illusory owned hand occur when the location of the real hand (and thus proprioceptive feedback) is kept constant. They found that the drift of the afterimage was dependent on experienced ownership over the fake hand (i.e.…”
Section: Positive Afterimagesmentioning
confidence: 99%
See 1 more Smart Citation